From mice to elephants: overturning the 'one size fits all' paradigm in marine plankton food chains. (27th April 2015) - Boyce, Daniel G.; Frank, Kenneth T.; Leggett, William C.; Wootton, Tim
Abstract It is widely believed that consumer control is a weak regulator of marine phytoplankton communities. It remains unclear, however, why this should be the case when marine consumers routinely regulate their prey at higher trophic levels. One possibility is that the weak consumer control of phytoplankton communities results from the inability of field researchers to effectively account for consumer–prey trophic relationships operating at the scale of the plankton. We explored this issue by reviewing studies of trophic control in marine plankton. Experimental studies indicate that size is a critical determinant of feeding relationships among plankton. In sharp contrast, of the 51 field studies reviewed, 78% did not distinguish among the sizes or species of phytoplankton and their consumers, but instead assumed a general bulk phytoplankton–zooplankton trophic connection. Such an approach neglects the possibility that several trophic connections may separate the smallest phytoplankton (0.2 μm) from the larger zooplankton (~ 1000 μm), a remarkable size differential exceeding that between a mouse (~10 cm) and an elephant (~2500 cm). The size‐based approach we propose integrates theory, experiments and field observations and has the potential to greatly enhance our understanding of the causes and consequences of recently documented restructuring of plankton communities.